2012
DOI: 10.1002/jrs.4136
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman scattering and fluorescence emission of gold nanoparticle–multiwalled carbon nanotube hybrids

Abstract: Multiwalled carbon nanotubes (MWCNTs) are grafted with gold (Au) nanoparticles of different sizes (1-12 and 1-20 nm) to form Au-MWCNT hybrids. The Au nanoparticles pile up at defect sites on the edges of MWCNTs in the form of chains. The micro-Raman scattering studies of these hybrids were carried using visible to infrared wavelengths (514.5 and 1064 nm). Enhanced Raman scattering and fluorescence is observed at an excitation wavelength of 514.5 nm. It is found that the graphitic (G) mode intensity enhances by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…This finding is in line with reports by Correa‐Duarte et al who state that the adsorption of metal nanoparticles on CNTs is often problematic since the extremely high curvature of the involved species hinders the formation of dense coatings in which the nanoparticles can be in mutual contact . Likewise, this observation agrees with reports about the preservation of the plasmonic properties of Au‐NP layers and chains on MWCNTs templates reported by Sharma et al as well as Au‐NP films deposited by micro contact printing on single CNT‐FET devices reported by Zhou et al Obviously, as shown by our experiments, the absence of pyrene in case “II” leads to a higher mobility of the colloids on the CNTs that lead to more dense and coating‐like decoration, whereas the pyrene interlinker allows a more sparse decoration with the Au‐NPs.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in line with reports by Correa‐Duarte et al who state that the adsorption of metal nanoparticles on CNTs is often problematic since the extremely high curvature of the involved species hinders the formation of dense coatings in which the nanoparticles can be in mutual contact . Likewise, this observation agrees with reports about the preservation of the plasmonic properties of Au‐NP layers and chains on MWCNTs templates reported by Sharma et al as well as Au‐NP films deposited by micro contact printing on single CNT‐FET devices reported by Zhou et al Obviously, as shown by our experiments, the absence of pyrene in case “II” leads to a higher mobility of the colloids on the CNTs that lead to more dense and coating‐like decoration, whereas the pyrene interlinker allows a more sparse decoration with the Au‐NPs.…”
Section: Resultssupporting
confidence: 93%
“…According to Guldi and co‐workers, the electrical photoresponse of such nanoconjugate‐based CNT‐FET devices can be explained by the fact that photoexcitation in the receptive part of the nanoconjugate incurs a rapid charge separation inside which causes a reduction of the electron‐accepting SWCNT and, simultaneously, the oxidation of the electron‐donating moiety . The electronic transport in such a hybrid device is hence modulated when the gate field is locally perturbated, for example, by stimulation of a plasmonic response . Hence, further environmental modulations to the latter such as molecular adsorption on the plasmonically active metal nanostructure can be an origin for further modulations of the electrical signal .…”
Section: Resultsmentioning
confidence: 99%
“…Among the several metal nanoparticles, AuNPs have attracted the attention of scientists due to their numerous applications in catalysis, sensing, imaging, and diagnostics [3][4][5][6]. 'AuNPs' is the area of research interest due to their unique properties such as tunable surface plasmon resonance (SPR), surface-enhanced Raman scattering, electrical, magnetic, thermal conductivity, antibacterial activity, chemical and biostability [7][8][9][10][11][12][13]. Besides this, the use of AuNPs as potential materials in the field of drug delivery and DNA delivery systems is noteworthy [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Sharma and coworkers used SERS and fluorescence emission to study gold NP‐multiwalled carbon nanotube hybrids. They found enhanced intensity of the D mode using 1064 nm excitation wavelength is related to the double resonance phenomenon and a shift in this mode occurs due to increased electron–phonon interactions near the Fermi level …”
Section: Introductionmentioning
confidence: 95%